Asthma – Inhaled Corticosteroids (ICS): different molecules - different devices – different treatment concepts: what really makes a difference? - Singla, Abhinav; Stegemann-Koniszewski, Sabine; Lücke, Eva; Kahlfuss, Sascha; Schreiber, Jens (Nepalese Respiratory Journal, 2024)
Bronchial asthma is a chronic, heterogeneous disease with different clinical phenotypes and inflammatory endotypes. Anti-inflammatory treatment with inhaled corticosteroids (ICS) has revolutionized the therapy of asthma and is indicated in almost all patients across all degrees of severity and therapy stages. Nevertheless, there is a broad spectrum of ICS molecules, dosages, combination partners, application concepts (maintenance therapy and/or as-needed therapy), and devices. Thus, there is a large number of variables, whose clinical significance is often unclear. This overview will therefore present clinically relevant aspects in the use of ICS and their combination partners.